Prevalence of late booking and factors of antenatal care among pregnant women in Sepang, Selangor, Malaysia - Nasir, Faizah (2022)
Introduction: Antenatal care (ANC) refer to the care of the women and fetus during pregnancy to monitor the maternal health and fetus growth. Ministry of Health Malaysia (MOH) recommended first ANC has to book within 12 gestational weeks. After 12 gestational weeks, it will be considered as late ANC booking. MOH has an expected target for late ANC booking should be less than 20%, however prevalence of late ANC booking in Malaysia still higher than targeted figure. Late ANC booking has been proved that will reduce the chances of detecting the maternal and baby health complication, eventually reducing the chances of providing treatment promptly. Up to now, there are few studies to investigate the factors associated with late booking on antenatal care in Malaysia. Objective: The objective of this study was to investigate the prevalence and factors of late booking on antenatal care among pregnant women in Sepang, Selangor. Methodology: The sample size of this cross-sectional study was 500 pregnant women in the first, second, and third trimesters who registered at government health clinics in Sepang District, Selangor. A simple random sampling method was used to recruit the respondents. Self-administrated questionnaires and performa were used to collect the data. Multiple logistic regression was used to determine factors associated with late ANC booking. Result: The response rate was 98.4%, with a total of 492 pregnant women recruited. The prevalence of late ANC booking was 27.6% (136). Factors statistically significant associated with late ANC booking were knowledge of antenatal care, parity, and mode of the previous delivery. Pregnant women with a poor knowledge on antenatal care (AOR=1.604, 95% CI:1.022,2.517, Pvalue= 0.040), higher parity (AOR=1.225, 95% CI:1.003,1.495, P-value=0.046), previous experience of spontaneous vaginal delivery (SVD) (AOR=2.855, 95% CI:1.227,6.645, P-value=0.015) and did not have any experience on delivery (AOR=2.906, 95% CI:1.147,7.364, P-value=0.025) were more likely to have late ANC booking. Conclusion: The prevalence of late ANC booking of this study was higher than MOH targeted. It is necessary to provide health education on the importance of early ANC booking to the new married couple to increase their probability of getting early antenatal care when they are pregnant. Appropriate health program can be devised for targeted population with certain characteristics (pregnant women with poor knowledge on antenatal care, higher parity, previous experience of spontaneous vaginal delivery (SVD) and did not have any experience on previous delivery) to reduce the probability of late ANC booking, eventually increasing the chances of detecting any complication during pregnancy and achieving the target settled by MOH.